Sex differences in resting-state cerebral activity alterations in internet gaming disorder - Sun, Yawen; Wang, Yao; Han, Xu; Jiang, Wenqing; Ding, Weina; Cao, Mengqiu; Du, Yasong; Lin, Fuchun; Xu, Jianrong; Zhou, Yan (Brain imaging and behavior, 2019)
Although evidence has shown that the prevalence rates of Internet gaming disorder (IGD) differ between males and females, few studies have examined whether such sex differences extend to brain function. This study aimed to explore the sex differences in resting-state cerebral activity alterations in IGD. Thirty male participants with IGD (IGDm), 23 female participants with IGD (IGDf), and 30 male and 22 female age-matched healthy controls (HC) underwent resting-state functional MRI. Maps of the amplitude of low-frequency fluctuation (ALFF) and functional connectivity (FC) were constructed. A two-factor ANCOVA model was performed, with sex and diagnosis as the between-subject factors. Then, post hoc pair-wise comparisons were performed using two-sample t-tests within the interaction masks. The Barratt Impulsiveness Scale-11 (BIS-11) was used to assess the behavioral inhibition function. We found that the ALFF values in the orbital part of the left superior frontal gyrus (SFG) were lower in IGDm than in HCm, which were negatively correlated with BIS-11 scores. IGDm also demonstrated lower connectivity between the orbital part of the left SFG and the posterior cingulate cortex (PCC), the right angular gyrus, and the right dorsolateral prefrontal cortex than HCm. Furthermore, IGDm had lower seed connectivity between the orbital part of the left SFG and the PCC than ICDf. Our findings suggest that (1) the altered ALFF values in the orbital part of the left SFG represent a clinically relevant biomarker for the behavioral inhibition function of IGDm; (2) IGD may interact with sex-specific patterns of FC in male and female subjects.